(3ChQGb aj GdEbJUGO GdSjGSj ddCReI GdEbJUGOjI GdQGgfI (B:s (3OQGSI (B/s - (3GdMeT, efjQs ((3OeTb(B: s (3efThQGJ GJMGO cJGH GdYQH(B, s, 1999)
(3GdQCSeGdjI, GdETJQGcjI(B- (3GdeNGWQ hGdJMOjGJ GdJj JhGLg GdhWf GdYQHj Ydi eTGQa GdbQf GdMGOj hGdYTQhf(B- (3GdJWhQGJ hGdJZjQGJ GdEbJUGOjI GdOhdjI hCKQgG Ydi GdEbJUGOGJ GdYQHjI(B- (3GfNaGV GSYGQ GdfaW hCKQg Ydi GbJUGOjGJ Ohd GdNdjL GdYQHj(B- (3GdJfejI hGdMQGc GdELJeGYj(B.s
Keywords: (3GdCReI GdEbJUGOjIs; (3GdEbJUGO GdSjGSjs